Konfigurasi Cekungan Tomori Berdasarkan Data Gayaberat - Tatang Padmawidjaja (Pusat Survei Geologi, 2019)
Geophysical research in Tomori Basin, Kolonodale Bay using the gravity method was carried out to identified anticline structural trap in associated with hydrocarbon prospect. The occurence of hydrocarbon seepage in some places, indicate that hydrocarbon have been formed although its distribution is not clearly known. The gravity Bouguer anomaly resulted two groups of rock units: the group of 40 mGal up to 120 mGal gravity anomaly represent ultramafic rocks, and group of 30 mGal up to -80 mGal gravity anomaly reflected a sedimentary rocks basin. The subsurface modeling of the rock density can be grouped into three layers: the Cenozoic (2.5-2.55 gr/cm³ density), the Mesozoic (2.6-2.7 gr/cm³ density), and the Basement ( 2.8-2.9 gr/cm³ density). Elongated and vertical closure are reflected by anomaly 0-2 mGal with density 2.5 gr/cm3 to 2:55 mGal which is supposed to be oil and gas structures. The Source rock is characterized by 0 to -10 mGal anomaly interpreted as oil kitchen at sub-basin area. Location of the reservoir rock is assumed in the Cenozoic layer on Salodik Group with density of 2.5 gr/cm³. The Basement is estimated at depth of 3.5-4 km, derived from the Group of metamorphic and volcanic rocks.Keyword: Gravity, basin, residual anomaly, fault, anticline. DOI:10.33332/jgsm.2019.v20.1.27-36